External balance of Kazakhstan and the impact of the current account on the national currency exchange rate - Khamazova, Karina; Bolotov, Ilya; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The aim of this bachelor's thesis is to analyze Kazakhstan's external balance and examine the impact of the current account on the exchange rate of the Kazakhstani tenge over the period from 2000 to 2024. The external balance of the country is analyzed using key macroeconomic indicators, such as the balance of payments, international investment position, and external debt, in accordance with international standards and criteria. The impact of the current account on the exchange rate is examined using econometric models, including regression analysis and Engle-Granger cointegration test. The thesis consists of three chapters: the first chapter focuses on the theoretical foundations of external balance; the second chapter contains an analysis of Kazakhstan's external balance; the third chapter focuses on econometric modeling and examining the relationship between the current account and exchange rate fluctuations.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses